Assessment of antimicrobial use and prescribing practices among pediatric inpatients in Zimbabwe. (16th November 2020) - Olaru, Ioana D.; Meierkord, Anne; Godman, Brian; Ngwenya, Crispen; Fitzgerald, Felicity; Dondo, Vongai; Ferrand, Rashida A.; Kranzer, Katharina
Abstract : This study aims to assess antimicrobial consumption in the pediatric department of a tertiary care public hospital in Zimbabwe. Clinical records of pediatric inpatients admitted to Harare Central Hospital over a 3-week period were reviewed prospectively. Antimicrobial consumption was described as days of therapy per 100 inpatient days (DOT/100 PD). Adherence of antimicrobial drug prescriptions to the National Guidelines was also evaluated. A total of 121 (93.1%) children were prescribed at least one antimicrobial out of 130 children admitted. The median age was 14 months (IQR: 3 − 48 months). Overall antimicrobial consumption was 155.4 DOT/100 PD (95% CI 146–165.2). The most frequently prescribed antimicrobials were benzylpenicillin, gentamicin and ceftriaxone. Prescriptions were adherent to national guidelines in 57.7% of children. This study shows that there is high antimicrobial drug usage in hospitalized children in Zimbabwe and a considerable proportion of prescriptions are non-adherent with national guidelines.